PENGARUH PERLAKUAN LEACHING TERHADAP SIFAT MEKANIK FILM LATEKS KARET ALAM BERPENGISI SELULOSA MIKROKRISTAL DARI AMPAS TEBU - Rismadhani Elita, Rojiyatul Ikhwani Lubis, Hamidah Harahap (Universitas Sumatera Utara, 2016)
Leaching process is one of many factors to raise up the mechanical properties of latex products. Studies on the effect of leaching on film natural rubber latex with the filler microcrystalline cellulose from bagasse with alkanolamide using different temperatures and times vulcanization has been done to produce the better mechanical properties such as strenght tensile and elongation at break. Filming of natural rubber latex is done by coagulants dyeing techniques. The study started with the process of pre-vulcanised natural rubber latex at 70 °C with a loading filler by 0 phr, 5 phr, 10 phr and 15 phr and followed by a vulcanization process at a temperature of 100 °C and 150 °C for 10 minutes and 20 minutes. The film result will be have leaching treatment using a solution of water and ammonia 1%. Test results of tensile strength of natural rubber latex film howed that the tensile strength of natural rubber latex film with microcrystalline cellulose as filler and alkanolamides after leaching less than the tensile strength of natural rubber lateks film before leaching